(untitled) (Global Journal of Computer Science and Technology, 2012)
Databases today are ranging in size into the Tera Bytes. It is an information extraction activity whose goal is to discover hidden facts contained in databases. Typical applications include market segmentation, customer profiling, fraud detection, evaluation of retail promotions, and credit risk analysis. Major Data Mining Tasks and processes include Classification, Clustering, Associations, Visualization, Summarization, Deviation Detection, Estimation, and Link Analysis etc. There are different approaches and techniques used for also known as data mining models and algorithms. Data mining algorithms task is discovering knowledge from massive data sets. In this paper, we are focusing on Classification process in Data Mining.